PENGARUH LINGKUNGAN SEKOLAH ISLAMI TERHADAP PENUMBUHAN KARAKTER ISLAMI ANAK TARBIYATUL ATHFAL TA AL KAUTSAR KOTA MALANG - Ratna Dewi; Eko Setiawan; Ika Anggraheni (UNISMA, 2022)
Children who are in Islamic school institutions usually also have an Islamic character. But usually they change when they are in the home environment. So there is a need for collaboration between educators and parents. The goal is to find out the influence of the Islamic school environment on the growth of Islamic character..This research includes quantitative research. Analysis of the data used is descriptive quantitative analysis, analysis of prerequisite tests: normality and linearity tests and simple linear regression analysis. The analytical tool used is an analysis with SPSS 24.The results showed that the average value of the Islamic character of the children of group A Tarbiyatul Athfal Malang City as a whole was 3.33. This value is in the good category. The characters of group A children grow because of the guidance from their parents. Results of simple linear regression analysis show that the significance value is 0.714 > 0.05, while the results of hypothesis testing can be seen that the t arithmetic value is -0.370 < 2.042. So Ho is accepted and Ha is rejected. It means that there is no influence between the Islamic school environment (X) and the growth of Islamic character (Y).